Characteristics and real-world medication persistence of people living with HIV treated with DTG/3TC or BIC/FTC/TAF: a hospital claims database study in Japan - Rie Kanamori; Nozomi Aoki; Akio Kanazawa; Mayumi Yuda; Nao Makino; Emi Ohata; Nobuyuki Fukui; Hirotake Mori; Hirohide Yokokawa; Toshio Naito (Frontiers in Medicine)
BackgroundAs the life expectancy of people living with human immunodeficiency virus (HIV) (PLWH) has improved, chronic disease burden and polypharmacy have increased in PLWH. Simplification of the antiretroviral therapy (ART) regimen for PLWH has become crucial. The real-world treatment patterns and medication persistence of the 2-drug single-tablet regimen (STR), dolutegravir/lamivudine (DTG/3TC), compared to bictegravir/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF) prescribed were investigated.MethodsThis retrospective, database study extracted data from a hospital-based medical claims database in Japan. The changes in ART distributions by year during the identification period between January 1, 2018 and December 31, 2021 were observed. Patients with disease record of HIV-1 infection and prescribed DTG/3TC or BIC/FTC/TAF as the first prescription of STR during the identification period were divided into two cohorts; DTG/3TC cohort and BIC/FTC/TAF cohort, respectively. Patient without medication records more than 3 months and no future data more than 6 months were excluded. Patients’ characteristics were compared between the DTG/3TC cohort and the BIC/FTC/TAF cohort by Mantel–Haenszel test to adjust for age. Medication persistence was compared between the two cohorts by evaluating the continuation rates using Kaplan–Meier methods, using the log-rank test to assess the difference between the Kaplan–Meier curves. The median time-to-first prescription was compared between the two cohorts by Kaplan–Meier methods.ResultsPrescriptions of DTG/3TC and BIC/FTC/TAF increased steadily from 2019 to 2021 after the release year of each STR. There was no significant difference in the time-to-first prescription (p = 0.3). A total of 959 patients were included, with 120 patients and 839 patients on DTG/3TC and BIC/FTC/TAF, respectively. The proportion of dyslipidemia at baseline was significantly higher in the DTG/3TC cohort than in the BIC/FTC/TAF cohort after adjusting for mean age (p = 0.002). There was no significant difference in medication persistence between the two cohorts (p = 0.91).ConclusionThis study showed that DTG/3TC was likely to be selected for elderly patients and those with chronic disease in real-world clinical practice, which seems in accordance with the treatment strategy recommended by guidelines. Comparable medication persistence was observed with both regimens, aligning with findings from other countries. The 2-drug single-tablet regimen DTG/3TC may be an important ART regimen for PLWH with multiple morbidities and polypharmacy in an aging society. Due to the limitations of the database, further research to assess viral loads, emergence of resistance and adverse events will be encouraged.